2020
DOI: 10.1177/0361198120926167
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causes of Social Exclusion Related to Mobility for Non-Motorized Households

Abstract: Using a lexicometric and qualitative data analysis of 57 semi-directed interviews with members of non-motorized households in the urban areas of Quebec City (Canada) and Strasbourg (France), this paper attempts to show whether living in a carless household in a car-dependent environment fosters feelings of social exclusion and if so, what the contributing factors are. Overall, a majority of respondents said they experienced feelings of social exclusion. Several factors were identified. The lack of consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, Kaufmann also points out that sometimes the available transport infrastructure is not compatible with the use of public transport, stressing the lack of policies that would support solving problems in this situation [29]. In turn, in another article, Villeneuve and Kaufmann emphasize the existence of exclusion also among non-motorized persons, pointing to the need to include them in various types of actions and communication campaigns [30]. Furthermore, many scientists stated that lack of access to transport results in poor access to goods and services and consequently leads to social exclusion [31][32][33][34][35][36].…”
Section: Social Exclusion In the Transport Areamentioning
confidence: 99%
“…Moreover, Kaufmann also points out that sometimes the available transport infrastructure is not compatible with the use of public transport, stressing the lack of policies that would support solving problems in this situation [29]. In turn, in another article, Villeneuve and Kaufmann emphasize the existence of exclusion also among non-motorized persons, pointing to the need to include them in various types of actions and communication campaigns [30]. Furthermore, many scientists stated that lack of access to transport results in poor access to goods and services and consequently leads to social exclusion [31][32][33][34][35][36].…”
Section: Social Exclusion In the Transport Areamentioning
confidence: 99%
“…They found that mode choice for work commuters is different from non-work commuters. The choice is supported by a sub-result of the survey by Villeneuve and Kaufmann (2020), according to which respondents confirmed preferences of car drivers in the labor market and at the political level. • Income tax expenses have been investigated, as Jeekel (2014) identified a spatial mismatch between living and working places for poorer and less educated households, noting that "many poorer households have cars, but their mobility comes at a price; a great part of their household income goes to car mobility."…”
Section: Potential Spatial Factors Associated With Car Dependencementioning
confidence: 90%